PEMBERDAYAAN KELOMPOK TANI DALAM MENINGKATKAN KUALITAS HASIL PERTANIAN DI DESA TEGAL KUNIR LOR KECAMATAN MAUK KABUPATEN TANGERANG - Asep saputra (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
The community empowerment is an effort to provide power or empowerment to the community. According to one expert in which he defines community empowerment, namely as the community's ability to develop and be interrelated so that it has the aim of finding new innovations in a community development. The community Empowerment to be precise in the field of agriculture and several Farmer Groups in Tegal Kunir Lor Village is one of the places that becomes objects to improve the quality of agricultural products. This research uses descriptive study and uses qualitative research methods. Based on the research results, empowerment and development needed to be increased towards planting and farmer motivation. The obstacles faced need to be conquered with the problem of not optimal irrigation or irrigation channels to the rice fields. The paddy fields and irrigation infrastructure and agricultural tools are not yet complete. So, it has not made the agriculture managed by the Farmer Group not able to optimize the paddy fields. Implementation of community spirit has not been optimal regarding several issues of awareness that had not been overcome. Enthusiasm of the community has not fully volunteered to enter the Farmer profession in the village of Tegal Kunir Lor so that only a few people, especially the elderly, are doing rice planting in the fields. Village Government, BPP Agricultural Extension Agency, Village Office Staff need to go counseling to encourage residents around the village. This effort is made to create a resilient agriculture that requires quality human resources and make a successor for future progress through agricultural extension activities with an approach farmer groups that support agriculture-based agribusiness system.